2013
DOI: 10.1371/journal.pone.0054427
|View full text |Cite
|
Sign up to set email alerts
|

Social Investigation and Long-Term Recognition Memory Performance in 129S1/SvImJ and C57BL/6JOlaHsd Mice and Their Hybrids

Abstract: When tested for their behavioural performance, the mixed genetic background of transgenic mice is a critical, but often ignored, issue. Such issues can arise because of the significant differences in defined behavioural parameters between embryonic stem cell donor and recipient strains. In this context, the commonly used stem cell donor strain ‘129’ shows ‘deficits’ in different paradigms for learning and long-term memory. We investigated the long-term social recognition memory performance and the investigativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Juvenile mice of both sexes of the C57BL/ 6JOlaHsd strain (25-38 days old) were used as a social stimulus. Extensive previous studies revealed that neither the age nor the sex of the juvenile significantly affects the recognition abilities of male adult experimental subjects [9,10].…”
Section: Animalsmentioning
confidence: 95%
See 1 more Smart Citation
“…Juvenile mice of both sexes of the C57BL/ 6JOlaHsd strain (25-38 days old) were used as a social stimulus. Extensive previous studies revealed that neither the age nor the sex of the juvenile significantly affects the recognition abilities of male adult experimental subjects [9,10].…”
Section: Animalsmentioning
confidence: 95%
“…[7][8][9]) and, therefore, considered to be suitable for our experiments. They were housed in groups of five per cage (size: 20 × 37 × 15 cm) under standard laboratory conditions with a 12 h:12 h light-dark cycle (light on: 07:00) for at least one week before starting the experiments.…”
Section: Animalsmentioning
confidence: 99%
“…The mice were group housed (2-3 mice/cage) till the beginning of the behavioral examination, when individual housing began to enhance social interest. Male juvenile (30-45-day-old) C57BL/6J mice were used as stimulus animals for the sociability and resident intruder test as previously suggested [90,91]. For RT-PCR C57BL/6J adult male mice were used from the same local colony.…”
Section: Animalsmentioning
confidence: 99%
“…The mice were group housed (2-3 mice/cage) until the beginning of the behavioral examination, when individual housing began to enhance social interest. Male juvenile (30-45-day-old) C57BL/6J mice were used as stimulus animals for the sociability and resident intruder tests as previously suggested [92,93]. For RT-PCR, C57BL/6J adult male mice from the same local colony were used.…”
Section: Animalsmentioning
confidence: 99%